Sensitivity Difussion Test of Cefixime against Neisseria gonorrhoeae from Female Sex Worker with Cervicitis Gonorrhea without Complication who Follow Periodic Presumptive Treatment (PPT) - Trisniartami Setyaningrum; Astindari Astindari; Hans Lumintang (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2017)
Background: Neisseria gonorrhoeae as etiology of gonorrhoeae infection is considered to be most concerned because of emerging antibiotic resistant strains that compromise the effectiveness of treatment. The emergence of antibiotic resistance has remained a challenge for a few decades. The third generation cephalosporins such as cefixime and ceftriaxone are now the first-line therapy in many region, however, the reduction of the susceptibility to cephalosporins is likely to emerge and spread. Purpose: To evaluate susceptibility of cefixime to Neisseria gonorrhoeae with diffusion test in uncomplicated cervicitis gonorrheae of female sex worker who following Periodic Presumptive Treatment’s program. Methods: The study design was descriptive observational cross sectional for 3.5 months from November 2012-February 2013 in Putat Jaya Public Health Center Surabaya. Results: There were 21 isolates of N. gonorrhoeae from 86 cervical secretions which were performed cefixime diffusion susceptibility test. Based on in vitro cefixime diffusion susceptibility test against N. gonorrhoeae isolates obtained 7 isolates (33.3%) were resistant to cefixime and 14 isolates (66.7%) sensitive to cefixime. From sensitive isolates, 5 of 14 isolates (35.7%) had inhibition zone with a diameter of 31 mm which is the minimum limit of cefixime ability to inhibit the growth rate of N. gonorrhoeae. Conclusions: There were found N. gonorrhoeae isolates that resistant to cefixime and some isolates with near of concentration maximal inhibition of cefixime with diffusion test. Thus it’s necessary to perform sentivity test of cefixime to N. gonorrhoeae using dilution test to obtain the resistance of N. gonorrhoeae to cefixime.